A suggested program of foundational conditioning exercises for age-group swimmers - Rushall, B. S.
The publication has been adapted from Rushall, B. S., Marsden, J., & Young, C. (1993). A suggested program of foundational conditioning exercises for age-group swimmers: A manual for coaches. NSWIMMING Coaching Science Bulletin, 2(1), 1-23. It's content: 1.A Suggested Program of Foundational Conditioning 2.Exercises for Age-group Swimmers Basic assumptions Implementing conditioning programs 3.Primary Conditioning Levels Level 1 Level 2 Level 3 Warning 4.Warm-up Running 5.A Continuous Weighted Bag/Medicine Ball Program Purpose Conduct Weighted bag/medicine ball exercises Training for weighted bag/medicine ball work 6.Static Training Exercises Training for static exercises 7.General Conditioning Exercises Exercises Training for general conditioning exercises 8.Time Allocation Overload Effort levels